MENCIPTAKAN KEPUASAN DAN LOYALITAS PELANGGAN MELALUI CITRA DAN SERVICE RECOVERY - Ken Sudarti; Iva Atika (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
Customer loyalty is considered by many service providers as an important source of competitive advantage. Enhanced cuatomer loyalty in service firms will lead to greater profitability. The objective of this research is to examine the effect of image of traditional food and service recovery on the effect on customer satisfaction and customer loyalty. Research involved 100 customers. By measuring criterion validity and reliability of image and service recovery, it found that both of them have a good validity and reliability for measuring the customer satisfaction and cuatomer loyalty. By using path analysis, the result revealed that image, service recovery and customer satisfaction have direct significantly effects on customer loyalty. The managerial implication of this research is that management of restaurant should build their image, implement service recovery program consistanly and create customer satisfaction to miantan their customer.